Differences in Cholesterol Levels in Coffee Drinkers Without Sugar and Coffee Drinkers With Sugar in The Work Area - Salsabila, Nadira; Khusuma, Ari; Jiwintarum, Yunan (Balai Publikasi Indonesia, 2024)
Indonesia is one of the coffee-producing countries as well as coffee bean exporters which ranks fourth in the world. Coffee is one of the most consumed beverages in the world which has become a major need for people without realizing it. Based on the results of previous studies that coffee drinkers using sugar can increase cholesterol levels. Excessive cholesterol in the body will accumulate in the walls of blood vessels and cause a condition called atherosclerosis, namely narrowing or hardening of the arteries. This condition is the forerunner of heart disease and stroke. This study aims to determine differences in cholesterol levels in coffee drinkers without sugar and coffee drinkers using sugar in the working area of Karang Pule. This research is an analytical observation using capillary blood samples of respondents who drink coffee without sugar and drink coffee with sugar. The data obtained in this study were recorded and presented in tabular form and analyzed descriptively. From the results of the study, it was found that the results of examining cholesterol levels in coffee drinkers without sugar were 15 people with an average cholesterol level of 169 mg/dl. Meanwhile, coffee drinkers using sugar were 15 people with an average cholesterol level examination of 242 mg/dl